‘Do they care?’: a qualitative examination of patient perspectives on primary care clinician communication related to opioids in the USA - Leif I Solberg; Katrina M Romagnoli; Anthony W Olson; Andrei Bucaloiu; Clayton I Allen; Lorraine D Tusing; Hillary A Henzler-Buckingham; Christina M Gregor; Laura A Freitag; Stephanie A Hooker; Rebecca C Rossom; Eric A Wright; et al. (BMJ Open)
Objectives This substudy’s objectives were to (1) examine the transferability of a four archetype framework (simplified pattern of prototypical features) for patients at high risk for opioid use disorder (OUD) developed from a previous study with a similar population; (2) explore how patient preferences for terminology can inform clinician communication strategies for patients with OUD across archetypes and (3) explore how patient perceptions of opioid risks can inform clinician communication strategies across patient archetypes.Design This qualitative study collected data via semistructured phone interviews with patients about views on opioid-related discussions with primary care clinicians. Qualitative data were coded using the Rigorous and Accelerated Data Reduction technique and analysed via iterative inductive/deductive thematic analysis.Setting 40 primary care clinics affiliated with two health systems (site1=Pennsylvania; site2=Minnesota, Wisconsin and North Dakota).Participants 40 adults meeting one of the following: OUD diagnosis; taking medication for OUD (MOUD) and ≥3 opioid prescriptions in the previous year.Results The aforementioned four archetype framework transferred well to the study sample and hinted at archetype differences in participant OUD-terminology preferences and opioid risk perceptions. Two additional archetypes of ‘in treatment/recovery for OUD and not taking MOUD’ and ‘in treatment/recovery for OUD and taking MOUD’ were identified. Participants best fitting archetypes 1–4 preferred clinicians to refrain from using addiction terminology to describe their relationship with opioids, finding the term ‘dependence’ as more appropriate and a signal that clinicians cared for patients. Participants who best first archetypes 5–6 felt ‘addiction’ was an appropriate, direct term that accurately described their condition, often using it themselves. Patients in all archetypes recognised risks of harm from using opioids, especially participants fitting archetypes 2, 5 and 6 who conveyed the greatest concern.Conclusion The modified six archetype framework may help clinicians tailor their communication and care for patients diagnosed with or at high risk for OUD.Trial registration number NCT04198428.